A "sweet-spot" for fluid-induced oscillations in the conditioning of stem cell-based engineered heart valve tissues. (8th December 2017) - Williams, Alexander; Nasim, Sana; Salinas, Manuel; Moshkforoush, Arash; Tsoukias, Nikolaos; Ramaswamy, Sharan
Abstract: Fluid-induced shear stresses are involved in the development of cardiovascular tissues. In a tissue engineering framework, this stimulus has also been considered as a mechanical regulator of stem cell differentiation. We recently demonstrated that the fluid-oscillating effect in combination with a physiologically-relevant shear stress magnitude contributes to the formation of stem cell-derived de novo heart valve tissues. However, the range of oscillations necessary to induce favorable gene expression and engineered tissue formation is unknown. In this study, we took a computational approach to establish a range of oscillatory shear stresses that may optimize in vitro valvular tissue growth. Taking a biomimetic approach, three physiologically-relevant flow waveforms from the human: (i) aorta, (ii) pulmonary artery and (iii) superior vena cava were utilized to simulate pulsatile flow conditions within a bioreactor that housed 3 tissue specimens. Results were compared to non-physiological pulsatile flow (NPPF) and cyclic flexure-steady flow (Flex-Flow) conditions. The oscillatory shear index (OSI) was used to quantify the fluid-induced oscillations occurring on the specimen surfaces. The range of mean OSI under the physiological conditions investigated was found to be 0.18 ≤ OSI ≤ 0.23. On the other hand, NPPF and Flex-Flow environments yielded a mean OSI of 0.37 and 0.11 respectively, which were 46% higher and 45% lower than physiological conditions. Moreover, we subsequently conducted OSI-based human bone marrow stem cell (HBMSC) culture experiments which resulted in preferential valvular gene expression and phenotype (significant upregulation of BMP, KLF2A, CD31 and α-SMA using an OSI of 0.23 in comparison to a lower OSI of 0.10 or a higher OSI of 0.38; p < .05). These findings suggest that a distinct range or a "sweet-spot" for physiological OSI exists in the mechanical conditioning of tissue engineered heart valves grown from stem cell sources. We conclude that in vitro heart valve matrix development could be further enhanced by simultaneous exposure of the engineered tissues to physiologically-relevant magnitudes of both fluid-induced oscillations and shear stresses.